2005
DOI: 10.1677/jme.1.01709
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional characterization of a type-I neurotensin receptor (NTR) and a novel NTR from the bullfrog brain

Abstract: Neurotensin (NT) is a tridecapeptide that functions as a neurotransmitter and neuromodulator in the nervous system. To date, three different types of NT receptor (NTR), NTR1, NTR2 and NTR3, have been identified only in mammalian species. In the present study we isolated the cDNAs for an NTR1 and a novel NTR in the bullfrog brain, designated bfNTR1 and bfNTR4 respectively. bfNTR1 and bfNTR4 encode 422-and 399-amino acid residue proteins respectively. bfNTR1 has a 64% amino acid identity with mammalian NTR1, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…There are three NT receptor subtypes, NT1, NT2 and NT3 that have been identified to date and evidence suggests that additional subtypes exist (Li et al, 2005; Mazella and Vincent, 2006). It is not known which receptors mediate the effects of NT on PPI but converging evidence most strongly implicates NT1 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…There are three NT receptor subtypes, NT1, NT2 and NT3 that have been identified to date and evidence suggests that additional subtypes exist (Li et al, 2005; Mazella and Vincent, 2006). It is not known which receptors mediate the effects of NT on PPI but converging evidence most strongly implicates NT1 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NTR2 cDNA together with NTR1 cDNA have been cloned in bullfrog [27]. NTR2 has also been identified in Xenopus tropicalis by a BLAST search [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown intracellular signaling pathways of mammalian NTR1 and NTR2 to be associated with intracellular Ca 2+ mobilization [10,19,27]. Chicken NT also induces Ca 2+ release from internal store, which is responsible for the contractile activity in the longitudinal smooth muscle of the rectum [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three NT receptor subtypes, NT1, NT2 and NT3 have been identified and there is evidence that additional subtypes exist [14,15]. NT1 and NT2 are high and low affinity G-protein coupled receptors (GPCRs), respectively.…”
Section: Introductionmentioning
confidence: 99%